PELATIHAN KOMPETENSI INTERPRETER DAN TERJEMAHAN BILINGUAL BERBASIS AUDIOVISUAL UNTUK MENDUKUNG PENEGAKAN KEBIJAKAN MARITIM INDONESIA - Margaret Stevani; Syahriati Fakhriah; Happy Kusuma Wardani (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service analyzed the relationship between legal interpretation and translation in cases of illegal fishing in Indonesia and its impact on law enforcement. Legal translation errors hindered international cooperation and the implementation of maritime policies. Using a qualitative approach and the PACTE (Process of Acquisition of Translation Competence and Evaluation) model, the activity involved undergraduate law students from Universitas Deli Sumatera in audiovisual tasks to translate and interpret courtroom clips related to illegal fishing. The analysis revealed key challenges in translating technical terms, pragmatics, and socio-cultural relevance. The study highlighted the importance of idiomatic translation and the Skopos approach to maintain legal accuracy. Interactive courtroom simulations were suggested to enhance legal practice understanding and support Indonesia's maritime policy effectiveness.